UPAYA GURU BIMBINGAN KONSELING DALAM MENANGANI KEJENUHAN BELAJAR SISWA DI SMP NEGERI BANDA ACEH - Mailita Mailita; M. Nazir Basyir; Dahliana Abdullah (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2016)
The study, entitled ‘Efforts of Counseling Teacher to Address Learning Overload of Student at SMP Negeri (State Junior High School) in Banda Aceh’ aimed to determine the learning overload level faced by students and measure counseling teachers took in dealing with them. The subjects were 6 counseling teachers and 130 students drawn randomly from three state junior high school in Banda Aceh. This study employed mixed methods combining both qualitative and quantitative methods. The data were collected through questionaires and interviews. The results indicated the students’ learning overload was in the medium category. This can be observed from frequinces of their answers in which 68 students, equivalent to 52,3%, were in the medium category. Teacher’ effort in handling the students has been very well through preventive, curative and development measure. The teachers have given group counseling for preventive effort, and individual counseling, direct and close communication with students for curative efforts. Development measure, on the other hand, was handled through psychological and mental development, personality development and intensive learning assistance.Keywords : Efforts of Counseling teachers, student learning overload